The Philosophical Essence of Humanism In The Renaissance - Tolibovich, Parpiyev (Pubmedia Social Sciences and Humanities, 2025)
In this article, the authors explore the philosophical nature of Renaissance humanism. According to the authors, humanism is not a monolithic movement, but a complex and multifaceted intellectual and cultural phenomenon that arose in response to the political, social, and cultural changes of that time. The authors explore key themes and concepts that have shaped humanistic thought, including the importance of individualism, reason, and the pursuit of knowledge, as well as the relationship between humanism and religion. It also examines the influence of the humanities on other fields of intellectual inquiry, such as art, literature, and science. Analyzing the philosophical underpinnings of humanism, the authors provide a nuanced and comprehensive understanding of this influential movement in Renaissance thought.